CD4+ Th1 to the rescue in HER-2+ breast cancer. (3rd October 2019) - Lowenfeld, Lea; Xu, Shuwen; Czerniecki, Brian J.
ABSTRACT: HER2 overexpression leads to downregulation of MHC class-I. CD4 + Th1 cytokines, IFNγ and TNFα, and monoclonal antibodies, trastuzumab and pertuzumab, restore MHC class-I expression, and enable CD8 + recognition and cytolysis. Restoration of the anti-HER2 CD4 + Th1 immune response in combination with HER2 targeted therapy appear to be critical to successful anti-HER2 CD8 + immunotherapy.